Academic Achievement in Biology with Suggested Solutions in Selected Secondary Schools in Kano State, Nigeria - Muhammad Barzani, Gasim; Mohd Ekhwan, Toriman; Auwalu Rabiu, Ali (2014)
The level of students’ academic achievement in Biology subject was found to be very poor. The declining performance of secondary school in Kano District is somewhat disappointing. The purpose of this paper is to identify the students’ academic achievements in biology subject. The sample comprises of one hundred respondents selected by using simple random sampling technique from the randomly selected five secondary schools. Data was collected by using questionnaire, documentary analysis of SSCE results for five years, observations and interviews. The statistical tools emphasized in analyzing the data were frequency table and simple percentages. However, if the government, NGOs, parents, teachers, students and other involved body can make proper implementation of the recommendations given in this paper, the level of students’ academic achievement in biology will reach to its maximum standard. The researcher is urging for more researches to be conducted in other regions in order to fix the problem nationwide.